Internalisasi Nilai-Nilai Keislaman Pada Remaja Masjid Nurul Falah Kelurahan Talang Kelapa Kota Palembang - Wijaya, Wijaya; Annur, Saipul; Ibrahim, Ibrahim (STAI Denpasar Bali, 2022)
This article discusses the Internalization of Islamic Values ​​in Youth at the Nurul Falah Mosque Block Kana Palembang. It is important to instill Islamic values ​​in Muslims, including mosque youth, as the next generation of the nation. The type of research used is qualitative with a descriptive approach. The method of collecting data is through interviews, observation and documentation. The data analysis technique begins with data reduction, then data presentation and finally data verification. Meanwhile, the technique for examining data integrity is through triangulation which consists of triangulation of time, sources and methods. The results obtained are Islamic Values ​​in Youth at the Nurul Falah Mosque Block Kana Palembang which have been well implemented, through the field of mosque worship. Some of the activities carried out are related to the cultivation of Islamic values ​​for mosque youth, namely the values ​​of faith, shari'ah values ​​and moral values. To internalize these Islamic values, several activities are carried out, namely Islamic studies which are held every Saturday night, then study of classic books on the first Sunday morning of every month, Islamic studies on national holidays, as well as routine activities every Friday night.